IMPLEMENTASI K3 DALAM MENINGKATKAN PRODUKTIVITAS KERJA DENGAN PENDEKATAN FAULT TREE ANALYSIS DI PT SA - Suhartoko, Cecep; Mas'ud, M. Imron (Lembaga Pengembangan Kinerja Dosen, 2021)
This study aims to analyze the application of occupational safety and health (K3) at PT SA. The OH&S inspection is directed to use the tree shortage investigation technique at PT''SA in the 2018-2020 period. The results of the study found that the main cause was caused by human activities and risky ecological conditions with the result that the estimated protected T esteem (Nts) in 2019 was known to be 0.47 and in 2020 it was -0.81. So that the current accident value tends to be reduced to the recurrence value of past accidents, where work accidents amounted to 297.45 in 2018, amounted to 122.05 I in 2019, and 16.54 in 2020.